'Malaria Blocks Development' Revisited: the Role of Disease in the History of Agricultural Development in the Eastern and Northern Transvaal Lowveld, 1890–1960. - Packard, Randall (Journal of Southern African Studies, 2001)
This article revisits assumptions about the impact of malaria on development by looking at the history of disease and agricultural development in the lowveld region of the former Transvaal Province of South Africa. It argues that the impact of both malaria and malaria control was not uniform but was mediated by race and class. Prior to World War II, large-scale white commercial farmers did very well in the lowveld despite the presence of malaria. Poorer whites, by contrast, suffered greatly from the disease and had little success in agriculture. African farmers, while not as successful as white commercial farmers, actually benefited economically from malaria in that the disease deterred more extensive white settlement in the region, leaving land available for African cultivation and herding. The benefits of malaria control following World War II were both limited and uneven. White commercial farmers extended citrus and sugar cultivation, but this was as much a product of rising commodity prices as effective malaria control. Large numbers of poorer whites did take advantage of the elimination of malaria and settled in the lowveld following the war. However, few of them made a living as farmers. Finally, postwar white settlement reduced farming opportunities for Africans and increased their dependence on wage labour.